Crossed Aphasia in a Dextral without “Minor” Hemisphere Signs - J. C. Marshall; P. W. Halligan (Behavioural Neurology)
A case of severe aphasia after right hemisphere stroke, confirmed by CT, in an unambiguously dextral patient is reported. The patient showed no limb apraxia, and performed well on a test of “closure” (Mooney faces). Extensive testing revealed no signs of visuo-spatial neglect. We conclude that “pure” crossed aphasia can occur in the absence of symptoms normally associated with right hemisphere lesions.